Dissociation of Response and Feedback Negativity in Schizophrenia: Electrophysiological and Computational Evidence for a Deficit in the Representation of Value - Morris, Sarah E.; Holroyd, Clay B.; Mann-Wrobel, Monica C.; Gold, James M. (Frontiers in Human Neuroscience, 2011)
Contrasting theories of schizophrenia propose that the disorder is characterized by a deficit in phasic changes in dopamine activity in response to ongoing events or, alternatively, by a weakness in the representation of the value of responses. Schizophrenia patients have reliably reduced brain activity following incorrect responses but other research suggests that they may have intact feedback-related potentials, indicating that the impairment may be specifically response-related. We used event-related brain potentials and computational modeling to examine this issue by comparing the neural response to outcomes with the neural response to behaviors that predict outcomes in patients with schizophrenia and psychiatrically healthy comparison subjects. We recorded feedback-related activity in a passive gambling task and a time estimation task and error-related activity in a flanker task. Patients’ brain activity following an erroneous response was reduced compared to comparison subjects but feedback-related activity did not differ between groups. Using computational modeling, we simulated the effects of an overall reduction in patients’ sensitivity to feedback, selective insensitivity to positive or negative feedback, reduced learning rate and a decreased representation of the value of the response given the stimulus on each trial. The results of the computational modeling suggest that schizophrenia patients exhibit weakened representation of response values, possibly due to failure of the basal ganglia to strongly associate stimuli with appropriate response alternatives.